2017
DOI: 10.1074/jbc.m117.782771
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein HuR contributes to neuroinflammation by promoting C-C chemokine receptor 6 (CCR6) expression on Th17 cells

Abstract: In both multiple sclerosis and experimental autoimmune encephalomyelitis (EAE), the C-C chemokine receptor 6 (CCR6) is critical for pathogenic T helper 17 (Th17) cell migration to the central nervous system (CNS). Whereas many cytokines and their receptors are potently regulated via post-transcriptional mechanisms in response to various stimuli, how CCR6 expression is post-transcriptionally regulated in Th17 cells is unknown. Here, using RNA-binding protein HuR conditional knock-out (KO) and wild-type (WT) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…During experimental TB, IL-27R regulates gene expression of Ccl20 and the accumulation of CCR6-expressing CD4 T cells C-C chemokine receptor 6 (CCR6) is expressed by Th17 cells 54,55 and is critical for the migration of murine Th17 cells into inflamed tissues. 56,57 Therefore, we were wondering whether during experimental TB the frequency of antigen-specific CCR6-expressing CD4 T cells is modulated in the absence of IL-27R-mediated signaling ( Fig. 7a).…”
Section: Resultsmentioning
confidence: 99%
“…During experimental TB, IL-27R regulates gene expression of Ccl20 and the accumulation of CCR6-expressing CD4 T cells C-C chemokine receptor 6 (CCR6) is expressed by Th17 cells 54,55 and is critical for the migration of murine Th17 cells into inflamed tissues. 56,57 Therefore, we were wondering whether during experimental TB the frequency of antigen-specific CCR6-expressing CD4 T cells is modulated in the absence of IL-27R-mediated signaling ( Fig. 7a).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the adoptive transfer of HuR-deficient Th17 cells leads to the delayed onset and amelioration of disease severity of EAE compared to controls [84]. In addition, HuR up-regulates the expression of CCR6 by promoting its translation and/or mRNA stabilization, enhancing the infiltration of Th17 cells into the CNS [85]. In another line of study, HuR in B cells has been shown to be important for the germinal center reaction and the class-switched antibody production via the regulation of splicing [86].…”
Section: Hurmentioning
confidence: 99%
“…Mechanistically, HuR stabilises Il17 mRNA and promotes T‐cell proliferation under the conditions of EAE. In addition, HuR upregulates the expression of the chemokine receptor CCR6 by promoting its translation and/or mRNA stabilisation, further enhancing the infiltration of Th17 cells into the CNS …”
Section: Rbps Orchestrate Immune Responses Via the Regulation Of Immumentioning
confidence: 99%
“…In addition, HuR upregulates the expression of the chemokine receptor CCR6 by promoting its translation and/or mRNA stabilisation, further enhancing the infiltration of Th17 cells into the CNS. 67 Inflammation in the central nervous system is also linked with iron metabolism. Members of the poly(rC) binding protein (PCBP) family are multifunctional proteins that serve as an iron chaperones and RNA binding proteins.…”
Section: Central Nervous System (Cns)mentioning
confidence: 99%